Pengaruh Transfer Pricing dan Kepemilikan Institusional Terhadap Tax Avoidance dengan Corporate Social Responsibility Sebagai Variabel Moderasi - Mutia Nurlaksani; Benarda Benarda (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to examine the effect of Transfer Pricing and Institutional Ownership with Corporate Social Responsibility as a Moderating. The population in this study consists of non-cyclicals consumer companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, totaling 130 companies. The sampling technique used is purposive sampling, and a sample of 26 companies was obtained with 130 observation data. The data source is secondary data with quantitative methods. The analysis technique used is multiple linear regression, with the help of the eviews version 13 application program. Based on the test results, this study states that (1) Transfer Pricing and Institutional Ownership have a joint or simultaneous effect on Tax Avoidance, (2) Transfer Pricing has a partial effect on Tax Avoidance, (3) Institutional Ownership does not have a partial effect on Tax Avoidance, (4) Corporate Social Responsibility is unable to moderate the relationship between Transfer Pricing and Tax Avoidance, (5) Corporate Social Responsibility is unable to moderate the relationship between Institutional Ownership and Tax Avoidance.